2020
DOI: 10.1096/fj.201902307rrr
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal miR‐103‐3p from LPS‐activated THP‐1 macrophage contributes to the activation of hepatic stellate cells

Abstract: Hepatic fibrosis occurs during chronic hepatic injury and is involved in hepatic stellate cells (HSCs) activated by several types of immune cells. Among the immune cells, hepatic macrophages and their crosstalk with HSCs play a vital role in all stages of hepatic fibrosis. Exosomes, which are 30‐150 nm lipid bilayer vehicles, can transfer specific lipid, nucleic acids, proteins, and other bioactive molecules. Exosomes can act as good communication between macrophages and HSCs. Herein, we investigated the role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 35 publications
6
71
0
Order By: Relevance
“…MiRNAs exert their effects by suppressing expression of their target genes [ 19 , 20 ]. In the present study, luciferase reporter assays revealed FOXO1 to be a direct target gene of miR-27a-3p in CI/R.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs exert their effects by suppressing expression of their target genes [ 19 , 20 ]. In the present study, luciferase reporter assays revealed FOXO1 to be a direct target gene of miR-27a-3p in CI/R.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic preconditioning can potentiate the protective effect of marrow stromal cells-derived exosomes on endotoxin-induced acute lung injury [28]. In addition, LPS pretreatment not only induced exosome secretion by macrophages but also enhanced the effects of macrophage-derived exosomes on the proliferation and activation of hepatic stellate cells [29]. Similarly, in the present study, we showed that preconditioning with IL-1β, one of the key proin ammatory factors induced by LPS, promoted the production of ADSC-Exos and affected the expression of miRNAs in exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal miR-155, a micro-RNA with pro-inflammatory activity, was elevated in the liver of mice subjected to LPS and/or the TLR9 ligand cytidine-phosphate-guanosine (CpG), suggesting its contribution to liver dysfunction ( 71 ). Exosomes might also contribute to chronic liver dysfunction after sepsis, as exosomal miR-103-3p from LPS-activated macrophages targeted Krüppel-like factor 4 (KLF4) to increase α-SMA, TGF-β, and Col1a1 of hepatic stellate cells, which can contribute to liver fibrosis ( 72 ). As a whole, exosomes induce acute and chronic liver dysfunction in sepsis by inducing local inflammation and remodeling, respectively.…”
Section: Impact Of Exosomes On Organ Systemsmentioning
confidence: 99%